2016
DOI: 10.1902/jop.2015.150364
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Periodontal Inflammation and Labor Triggers (Elevated Cytokine Levels) in Preterm Birth: A Cross‐Sectional Study

Abstract: Women with PTB demonstrated worse periodontal parameters and significantly increased GCF levels of IL-6 and PGE2 compared with those with FTB. Based on significant correlations among serum PGE2 and PD, CAL, and GCF TNF-α in PTB, periodontitis may cause an overall increase of labor triggers and hence contribute to preterm labor onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
0
31
0
5
Order By: Relevance
“…There are numerous studies showing that markers of inflammatory response are elevated in subjects suffering from periodontitis compared with healthy ones (Bretz et al, 2005;Passoja et al, 2010;Robati, Ranjbari, Ghafourian Boroujerdnia, & Chinipardaz, 2011). In the same direction, in order to understand the effect of periodontitis in various systemic conditions, studies were conducted in specific groups presenting comorbidities (Perunovic, Rakic, Nikolic, et al, 2016;Satpathy et al, 2015;Zhu, Lin, Zheng, & Chen, 2015).…”
mentioning
confidence: 99%
“…There are numerous studies showing that markers of inflammatory response are elevated in subjects suffering from periodontitis compared with healthy ones (Bretz et al, 2005;Passoja et al, 2010;Robati, Ranjbari, Ghafourian Boroujerdnia, & Chinipardaz, 2011). In the same direction, in order to understand the effect of periodontitis in various systemic conditions, studies were conducted in specific groups presenting comorbidities (Perunovic, Rakic, Nikolic, et al, 2016;Satpathy et al, 2015;Zhu, Lin, Zheng, & Chen, 2015).…”
mentioning
confidence: 99%
“…Atherosclerosis, a progressive disease of medium and large elastic and muscular arteries can lead to ischemic lesions of brain, heart or extremities and can result in thrombosis and infarction of affected vessels 4 . It is considered the primary cause of heart disease and stroke and is the underlying cause of around 50% of all deaths in western societies 15 .…”
Section: Discussionmentioning
confidence: 99%
“…who have concluded that the women with preterm birth compared to the women with term birth have poor periodontal status. [262728] This can be explained by the fact that periodontal disease may influence pregnancy outcome by the direct or indirect effect of periodontal pathogens on the developing fetus.…”
Section: Discussionmentioning
confidence: 99%